Brazil : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation with Brazil discusses that growth is projected at 0.8 percent in 2019 and to accelerate in 2020 conditional on the approval of a robust pension reform and favorable financial conditions. The current budget is guided by the federal expenditure ceiling, entailing a minor reduction of the structural primary balance in 2019. The review encouraged the authorities to step up implementation of structural reforms essential to raise potential growth, including improving the business environment, lowering trade barriers, and boosting productivity. Fiscal policy is expected to be mildly supportive in 2019 and subsequently turn moderately contractionary to respect the constitutional ceiling. Gross public debt is projected to peak in 2024 at 96 percent of gross domestic product. Brazil needs decisive structural reforms to raise potential growth, including tax reforms, privatization, trade liberalization, and measures to enhance the efficiency of financial intermediation. Given the high and increasing level of public debt, fiscal consolidation is essential. The government should preserve a broadly neutral fiscal stance in 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet